Exploring the use of constructive journalism techniques in Covid-19 health reporting by Bhekisisa and Spotlight (February to December 2020) - Hoek, Sarah Ruth (Stellenbosch : Stellenbosch University, 2026)
Thesis (MA)--Stellenbosch University, 2026.